Dampak Eksternalitas Balai Ternak Ayam Petelur di Kabupaten Aceh Besar - Muhammad Iqbal; Cut Risya Varlitya; Irwan Safwadi (Center for Research and Community Service (LPPM) University of Abulyatama, 2021)
This study aims to determine the impact of positive and negative externalities from the existence of laying hens on the community around the Service Technical Implementation Unit (UPTD) of the Blang Bintang Non-Ruminant Livestock Center (BTNR), Aceh Besar District, namely Data Makmur Village. The data analysis method used is descriptive qualitative with primary data through questionnaires to 38 respondents consisting of 36 percent working as entrepreneurs, 21 percent as farmers, 24 percent as private employees, builders, and homemakers. The remaining 19 percent are from other professions. The sampling method in the analysis is purposive sampling. The study results indicate that there are positive externalities from the UPTD BTNR, namely reducing the number of unemployed, creating jobs, increasing the income of the population, making socio-economic interaction relations better, and the crime rate decreasing. The effects of negative externalities include environmental pollution and declining public health. However, the negative externalities that impact the health of residents are more caused by the existence of a landfills which is also adjacent to residential areas.